2007
DOI: 10.4088/jcp.v68n1110
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Duloxetine 60 mg Once Daily in the Treatment of Pain in Patients With Major Depressive Disorder and At Least Moderate Pain of Unknown Etiology

Abstract: Depression is generally diagnosed through the core mood symptoms and a variety of associated emotional and physical symptoms that are persistent during a 2-week period. In primary care, the diagnosis of depression is complicated due to the combination of core mood symptoms and associated symptoms such as painful physical symptoms. 1,3-5 Among primary care patients, 65% of patients with MDD were shown to have some type of painful physical symptoms. 6,7 A greater severity of painful physical symptoms, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 47 publications
2
58
0
2
Order By: Relevance
“…The mean diff erence in time to response concerning pain vs. mood of 1.3 days is smaller than what has been reported in other studies [ 20 ] (diff erence of 7 days for overall pain and 15.5 days for back pain), but the literature on this topic is not consistent and there have been other studies reporting no such diff erences [ 27 ] . In these studies, however, mood and pain were assessed mostly by weekly ratings (e. g., [ 28 ] ) and not on a daily basis as in our study. It might be argued that the temporal separation of the mean improvement curves suggests that pain and mood change at least in part independently from each other [ 29 ] .…”
Section: Discussion ▼mentioning
confidence: 99%
“…The mean diff erence in time to response concerning pain vs. mood of 1.3 days is smaller than what has been reported in other studies [ 20 ] (diff erence of 7 days for overall pain and 15.5 days for back pain), but the literature on this topic is not consistent and there have been other studies reporting no such diff erences [ 27 ] . In these studies, however, mood and pain were assessed mostly by weekly ratings (e. g., [ 28 ] ) and not on a daily basis as in our study. It might be argued that the temporal separation of the mean improvement curves suggests that pain and mood change at least in part independently from each other [ 29 ] .…”
Section: Discussion ▼mentioning
confidence: 99%
“…With 60 mg/day of DLX in elderly MDD patients, the most frequently reported ADRs were dry mouth and moderate nausea, and at rates similar to those reported with several SRIs in older patients, and without appreciable increases or decreases in blood pressure or pulse than with a PBO or SRIs (Raskin et al, 2008a). However, other studies have reported higher rates of treatment-related nausea with DLX than PBO or SRIs (Detke et al, 2002a,b;Goldstein et al, 2004;Brannan et al, 2005;Perahia et al, 2006bPerahia et al, , 2008Brecht et al, 2007;Lee et al, 2007;Nierenberg et al, 2007;Dunner et al, 2008). In one open label trial with more prolonged treatment with DLX, newly arising ADRs were rare, but some symptoms have been reported (Dunner et al, 2008) to begin or increase (e.g., decreased libido, abnormal orgasms, weight-gain orloss, hypersomnia, night-sweats, nightmares or early awakening, increased blood pressure, tachycardia, tremor, dizziness or unsteadiness, aggression, hypomania, or suicidal ideation).…”
Section: Risks Of Adverse Effectsmentioning
confidence: 75%
“…Data analyses were based on standard commercial statistical programs (Stata.8 1 , StataCorp, College Station, TX; Statview.5 1 , SAS, Cary, NC). Brecht et al, 2007;Khan et al, 2007;Lee et al, 2007;Nierenberg et al, 2007;Raskin et al, 2007Raskin et al, , 2008aWade et al, 2007) (Tables 2 and 3). Age averaged 44.1 AE 6.7 years; one trial selected patients averaging 73 years of age (reported in Raskin et al, 2007Raskin et al, , 2008a Abbreviations: DLX, duloxetine; PBO, placebo; SRI, serotonin-reuptake inhibitor comparators (FLX…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 No definitive treatment for BMS has been established, to date. The current approach combines medications, nerve block and supportive psychotherapy.…”
Section: Discussionmentioning
confidence: 99%